Die lang pad van bekering. Deel 1. Die opkoms van die kategumenaat in die Patristieke tyd - Wepener, CJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2007)
In this series of articles the story of the catechumenate is told. Starting with the Apostolic times and diachronically following the development of this process through the centuries, the story of it’s origin, the so-called golden age, it’s demise as well as the recent rediscovery of the catechumenate is described and commented on. The study aims at commenting on teaching, ethics and mission from a liturgical historical point of view. By means of a historical reconstruction of the ritual form as well as didactic content of the catechumenate, several questions are addressed. Firstly it is being asked what (if any) impact the process of the catechumenate can have on a discrepancy between faith and deeds (Ethics), secondly, how Christians were initiated into the early church before and after 312 (Mission), and thirdly what we can learn about the manner in which instruction occured in the catechumenate (Teaching)? The hypothesis of this research is that insight into the process of the catechumenate can help the church today to forge a closer connection between faith and life by means of a similar ritual-didactic process of conversion and initiation. In the first article the catechumenate is reconstructed as it developed in the first centuries, up to 312. In the second part of this series the historical inquiry will be continued from 312 onwards and through the Middled Ages. In part 3 the Reformation period will be dealt with in some more detail, and in part 4 an ecumenical survey will be conducted regarding the rediscovery of the catechumenate in the last decades. In every article some guidelines will be distilled that will all be systematised in a practical-theological model in part 5.